Ultra-low detection limit chemoresistive NO2 gas sensor using single transferred MoS2 flake: an advanced nanofabrication. Issue 51 (22nd November 2022) - Hong, Hoang Si; Hoang, Tran Vinh; Huong, Nguyen Thanh; Nam, Nguyen Hoang; Thinh, Dao Duc; Hue, Nguyen Thi; Thuan, Nguyen Duc
Abstract : In this work, a method of fabricating a NO2 nano-sensor working at room temperature with a low detectable concentration limit is proposed. Abstract : In this work, a method of fabricating a NO2 nano-sensor working at room temperature with a low detectable concentration limit is proposed. A 2D-MoS2 flake is isolated by transferring a single MoS2 flake to SiO2 /Si substrate, followed by applying an advanced e-beam lithography (EBL) to form a metal contact with Au/Cr electrodes. The resulting chemoresistive nano-sensor using a single MoS2 flake was applied to detect a very low concentration of NO2 at the part-per-billion (ppb) level. This result is obtained due to the ability to create microscopic nano-sized MoS2 gaps using e-beam lithography (300 nm–400 nm). Experimental results also show that the sensor can capture changes in concentration and send the information out extremely quickly. The response and recovery time of the sensor also reached the lowest point of 50 and 75 ms, outperforming other sensors with a similar concentration working range.